KEPASTIAN HUKUM CRYPTOCURRENCY SEBAGAI ALAT PEMBAYARAN DI INDONESIA - Febrianto, Andre; Ismail; Iryani, Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The rapid development of cryptocurrency as a global digital financial instrument has created legal challenges, particularly concerning its status as a medium of exchange. In Indonesia, the legal standing of cryptocurrency faces duality and ambiguity. On one hand, the Commodity Futures Trading Regulatory Agency (BAPPEBTI) regulates and recognizes cryptocurrency as a tradable commodity on the futures exchange. On the other hand, Bank Indonesia (BI) strictly prohibits its use as a legal tender, based on Law Number 7 of 2011 concerning Currency, which affirms the Rupiah as the sole legal medium of payment. This study aims to analyze the legal consequences of using cryptocurrency as a means of payment in Indonesia and to formulate a regulatory concept that can realize legal certainty. This research employs a normative legal research method with a qualitative approach. The data utilized includes primary, secondary, and tertiary legal materials. The results of the study indicate that the use of cryptocurrency as a means of payment can result in the cancellation of a private agreement (based on Article 1337 of the Indonesian Civil Code), administrative sanctions from BI and BAPPEBTI, and potential criminal exposure related to Money Laundering Offenses (TPPU). To achieve legal certainty, an integrated regulatory framework is required, encompassing: (1) clear classification of cryptocurrencies (payment, utility, security tokens); (2) the establishment of a special law regarding digital assets; (3) coordination among regulatory institutions (BI, OJK, BAPPEBTI, Kominfo); (4) effective consumer protection and dispute resolution mechanisms; and (5) the integration of Anti-Money Laundering (AML) and Know Your Customer (KYC) principles. Policy recommendations include strengthening socialization efforts, adopting a regulatory sandbox, and accelerating the Central Bank Digital Currency (CBDC) project, the Digital Rupiah.